Korelasi Perilaku Konsumsi Sugar Sweetened Beverage dengan Kejadian Overweight pada Remaja: Correlation between Sugar Sweetened Beverage Consumption Behavior and Overweight Incidence in Adolescents - Fuadah, Dina Zakiyyatul; Hayati, Farida; Firnanda, Muhammad Erick (Chakra Brahmanda Lentera Institute, 2026)
The modern world faces a double burden of malnutrition, where a country experiences two nutritional problems, namely undernutrition and overnutrition. One of the common nutritional problems among adolescents is obesity. Obesity is thought to be caused by the habit of consuming sugary drinks. This study aims to identify the relationship between the habit of consuming sugary drinks and the incidence of obesity in adolescents. This research approach uses correlation analysis with a cross-sectional method. The sampling technique used total sampling, with a sample size of 94 junior high school students. The research variables were consumption of sugar-sweetened beverages (SSBs) and the incidence of overweight. Data analysis was performed using Spearman's nonparametric statistical test. The results showed that most respondents (73.4%) were in the high consumption category. Based on the nutritional status of the respondents, only a few (22.3%) were obese. The correlation between sweetened beverage consumption and obesity had a p-value of 0.796 > 0.05, indicating no relationship between the two variables. The absence of a positive correlation between sweetened beverage consumption and obesity is likely due to various factors that influence Body Mass Index, glucostatic theory, and individual energy compensation mechanisms.